INFORMATION TECHNOLOGY FOR TRAINING THE PERSONNEL OF ENTERPRISES BY MEANS OF VIRTUAL REALITY - KRYVENCHUK, Yurii; SHCHUR, Hlib (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The use of virtual reality in industrial training reduces costs and risks, supporting more and more diverse use of experiential training sessions. This approach enables the trainer to structure the entire virtual reality training course in an immersive environment by defining its sub-components, models, tools and settings, as well as defining the actions that the participants should perform. Actions taken are recorded and coordinated with those specified by the trainer. In the industrial sector, the ability to apply to requests with a high degree of customization and complexity implies a longer cycle time. The application of virtual reality (VR) is a promising approach that will help minimize errors and increase safety. Virtual reality environments are also applied to operational tasks in industrial settings as an experiential learning approach that has shown good results in areas such as occupational safety, medicine, maintenance and mining. In addition, the use of a virtual environment for the implementation of learning activities has a wide range of advantages compared to learning in a real context, as well as reducing costs and risks, better control of the learning process (for example, planning lessons and determining the complexity of actions), facilitating experiential and situational learning, ability. to ensure repetition of simulations performed by trainees, empowerment of self-learning processes and eliciting emotions, promoting student interest and engagement. Virtual reality provides new sources of efficiency for all organizations. It can also significantly reduce the costs of training, services, installation, design and other parts of the value chain. It can also significantly reduce production costs by reducing physical space requirements. The key indicators for the implementation of VR in the educational process are reduction of study time; мore users who can perform the operation without previous experience; reduction of training costs; reducing the risk of injury.
Keywords: personnel training; virtual reality; enterprise